2002
DOI: 10.1128/cdli.9.4.883-891.2002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiepitope Polyproteins in Serodiagnosis of Active Tuberculosis

Abstract: Screening of genomic expression libraries from Mycobacterium tuberculosis with sera from tuberculosis (TB) patients or rabbit antiserum to M. tuberculosis led to the identification of novel antigens capable of detecting specific antibodies to M. tuberculosis. Three antigens, Mtb11 (also known as CFP-10), Mtb8, and Mtb48, were tested together with the previously reported 38-kDa protein, in an enzyme-linked immunosorbent assay (ELISA) to detect antibodies in TB patients. These four proteins were also produced as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 42 publications
8
78
1
3
Order By: Relevance
“…1). Similar results were reported with the chimera construction expressing 38 kDa, CFP-10 and MTB-8 (17).…”
Section: Discussionsupporting
confidence: 77%
“…1). Similar results were reported with the chimera construction expressing 38 kDa, CFP-10 and MTB-8 (17).…”
Section: Discussionsupporting
confidence: 77%
“…The TbF6/DPEP antigen association showed better results, with reagent serum samples in 44 (85%) of the patients. This sensitivity is in agreement with that of other studies for the same association using serum from Brazilian patients [21] and is similar to the sensitivity described by Cole et al [28] in a study carried out on patients with pulmonary tuberculosis in China. These authors found a sensitivity of 89% for smear-positive patients, and of 74% for smear-negative patients for the 38 kDa antigen.…”
Section: Discussionsupporting
confidence: 81%
“…It is a polyprotein designed to incorporate four genes of interest (Mtb8, 38 kDa, Mtb11 and Mtb 48) into a single expression vector [21]. The recombinant antigen DPEP (Corixa® Co.) is a proline-rich protein that has been identified as the MPT 32 antigen.…”
Section: Recombinant Antigensmentioning
confidence: 99%
“…Although the biological function of Ca dodecin is yet to be determined, identification of Ca dodecin as an immunodominant sero-antigen emphasizes a possible role in host response. 24,25 The antigenicity of Ca dodecin and its use in detecting Mtbspecific sera from TB patients 26 also suggests that Ca dodecin could be a secreted or shed antigen. 27,28 In addition, the characteristics of the calcium-binding pocket in Ca dodecin suggest that the dodecins could be used as a scaffold to create custom designed metal and flavin binding sites.…”
Section: Resultsmentioning
confidence: 99%